In Vitro and In Vivo Characterization of the New Analgesic Combination Beta-Caryophyllene and Docosahexaenoic Acid. (7th July 2014) - Fiorenzani, Paolo; Lamponi, Stefania; Magnani, Agnese; Ceccarelli, Ilaria; Aloisi, Anna Maria
Abstract : Beta-caryophyllene (BCP) and docosahexaenoic acid (DHA) are components of several plants with documented anti-inflammatory and analgesic effects in animal pain models. In the present study, in vitro and in vivo tests were carried out to evaluate their effects, alone or in combination, during long-lasting administration in a model of persistent pain. IR spectra of the two compounds were obtained to determine their chemical stability and then in vitro toxicity was evaluated in fibroblasts and astrocytes. In the in vivo tests, the analgesic effects of BCP and BCP+DHA were determined in male rats subjected to a model of persistent recurrent pain (three repetitions of the formalin test once a week) to mimic recurrent pain. Both substances were administered per os in almond oil for 2 weeks. Gonadal hormones were determined at the end of the tests to evaluate treatment-induced effects on their levels. BCP changed fibroblast and astrocyte survival in a dose-dependent manner and the effect was counteracted by DHA coadministration. In the in vivo tests, pain responses were significantly decreased in the BCP and BCP+DHA groups with respect to OIL after 1 and 2 weeks of treatment. Estradiol and testosterone levels were increased only in the BCP group. In conclusion, BCP alone or at lower concentration in combination with DHA was efficacious in modulating pain, showing a clear analgesic activity.